Nanocrystalline high-entropy alloys. Issue 18 (22nd August 2017) - Koch, Carl C.
Abstract: Abstract : This article is a review of research on nanostructured high-entropy alloys with emphasis on those made by the severe plastic deformation methods of mechanical alloying and high-pressure torsion. An example of thin film refractory metal alloys made by magnetron sputtering is also presented. The article will begin with a discussion of the seminal research of B.S. Murty and co-workers who first produced nanocrystalline high-entropy alloys by mechanical alloying of powders. This will be followed by a listing of research, in mostly chronological order, of mainly 3d transition metal alloys made nanocrystalline by mechanical alloying. Research on the well-studied Cantor alloy, from the literature and the author's laboratory will be presented. The author's and co-worker's research on a low-density high-entropy alloy with single-phase fcc or hcp structure and an extremely high strength (hardness)-to-weight ratio will be described.